Study on the Effect of busing Road milling waste as a partial Replacement for Coarse Aggregate on the Compressive Strength and Workability of Concrete - Dr. Naji Amhimmid Salih (African Journal of Advanced Pure and Applied Sciences, 2025)
The study investigates the effect of partially replacing coarse aggregate with asphalt milling byproduct on the properties of concrete mixtures. Several replacement ratios ranging from 0% up to 50% were tested, measuring slump (mm) and average compressive strength at 7 and 28 days. Results indicated that increasing the replacement ratio led to a gradual reduction in slump, decreasing from 90 mm at 0% replacement to 40 mm at 50% replacement. A continuous decline in compressive strength was also observed at both 7 and 28 days, dropping from 21 MPa and 31 MPa to 13 MPa and 18.5 MPa, respectively, with higher replacement percentages. The study concludes that using asphalt milling byproduct as a partial replacement for coarse aggregate reduces compressive strength and durability of the concrete mixture, while increasing slump loss. Therefore, precise control of replacement ratios is essential to optimize concrete performance and minimize adverse effects.